Application of carbon fiber reinforced polymer laminate for strengthening reinforced concrete T-beam /Muhammad Mukhlesur Rahman - Muhammad Mukhlesur, Rahman (2012)
Most of the researches on strengthening so far had been focused on rectangular reinforced concrete (RC) beams. Researches on strengthening of RC T-beams are rather limited. This study focuses on the application of carbon fibre reinforced polymer (CFRP) laminate for strengthening the tension zone of RC T-beam constrained by the presence of a stump (representative of a column) and the effect of varying the length of the strengthening laminates. Three different orientations of the CFRP laminates were tested to evaluate the best orientation. The behaviour of RC T-beams (with stump) flexurally strengthened both in tension and compression zones were also studied here. In addition, FEM (non-linear finite element analysis) was applied to model the experimental results. To evaluate the effectiveness of the proposed strengthening method, a total of eight RC T-beams were fabricated and tested. Four of them were cast with a column stump in the midspan to provide constraints for the application of CFRP laminates. The other four beams were cast without any column stump. The following orientations were chosen. Orientation 1 was the full application of CFRP laminate along the centre of beam length assuming no stump was present. Orientation 2 was the full application of CFRP laminate alongside the stump parallel to beam length and Orientation 3 was the application of CFRP laminate around the stump and a continuous strip from the side of the stump to the ends of the beam. The beams were tested using the three point bending test set-up. The results showed that the load carrying capacities of the tension zone strengthened beams were increased by about 50% compared to un-strengthened beams. The length of the CFRP laminate recommended in the Technical Report 55 did not prevent end peeling but it did increase the load bearing capacity of the RC T-beam. The most suitable orientation of CFRP laminate determined was Orientation 2. The load carrying capacity had increased by about 70% compared to un-strengthened beam by strengthening both the tension and compression zone. The FEM analyses were in good agreement with the experimental results.